Performance Improvement of an Integrated Collector Storage Solar Water Heater by Using an Additional Glass Cover: A Numerical Study - Angham F. Abed; Noora A. Hashim; Ruaa B. Dahham; Esam H. Alkaldy (Iraqi Journal of Industrial Research)
This paper describes the analysis of a solar storage water heating system, emphasizing its cost-effectiveness and integrated design. The study employs numerical analysis to assess and optimize the performance of a rectangular solar collector with an added glass cover and an internal horizontal barrier. Using COMSOL software, a three-dimensional modeling study was conducted in the Kufa-Najaf climate on May 9th. The analysis focused on fundamental convection equations governing mass, momentum, and energy conservation. Temperature and velocity distributions were obtained at 13:30 PM, revealing a peak storage water temperature of 56.3 °C. The additional glass cover-barrier storage collector, set at a 60° angle, exhibited the highest stored energy at 2065.6 W, surpassing the conventional storage collector at 1007.06 W. Furthermore, the model demonstrated an increased instantaneous efficiency of 58.3%, compared to 28.4% for the conventional collector. The simulation results align well with previous findings, showing a maximum mean absolute percent error (MAE) of 4.5%.